2019
DOI: 10.17305/bjbms.2019.4131
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns and prognostic value of miR-210, miR-494, and miR-205 in middle-aged and old patients with sepsis-induced acute kidney injury

Abstract: Septic patients suffer a ‘cytokine storm’ from proinflammatory cytokines, chemokines and other inflammatory mediators, resulting in acute kidney injury (AKI) and death. The purpose of the present study was to determine the expression patterns of microRNA-210 (miR-210), miR-494, and miR-205 in middle-aged and old patients with sepsis-induced AKI and to evaluate their association with patient prognosis. Serum blood urea nitrogen (BUN), creatinine (Cr) and cystatin C levels were determined in peripheral venous bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The interaction between lncRNAs and microRNAs was delineated to elaborately modulate the elusive balance of survival and programmed death (23). In the present study, through the evaluation of cell apoptosis in the Cisplatin-stimulated HK-2 cells, it was revealed that the down-regulation of GAS5 signi cantly correlate with the alleviation of cell apoptosis, while that of miR-205-5p conversely delivered a apoptosis-promoting effect, which conforms to the revealed role of miR-205-5p to elevate the resistance of oxidative and endoplasmic reticulum stresses and consequently be in favor of cell survival recent years (24,25). Furthermore, the administration with miR-205-5p mimic also suppressed the severe apoptotic procedures in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…The interaction between lncRNAs and microRNAs was delineated to elaborately modulate the elusive balance of survival and programmed death (23). In the present study, through the evaluation of cell apoptosis in the Cisplatin-stimulated HK-2 cells, it was revealed that the down-regulation of GAS5 signi cantly correlate with the alleviation of cell apoptosis, while that of miR-205-5p conversely delivered a apoptosis-promoting effect, which conforms to the revealed role of miR-205-5p to elevate the resistance of oxidative and endoplasmic reticulum stresses and consequently be in favor of cell survival recent years (24,25). Furthermore, the administration with miR-205-5p mimic also suppressed the severe apoptotic procedures in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…Recently, the study showed that circulating miR-494 increased significantly in children with AKI after cardiopulmonary bypass [ 68 ]. Of note, emergent data suggested that the higher level of serum miR-210 and miR-494 in patients with sepsis-induced AKI were also correlated with poor prognosis and survival [ 69 ]. Additionally, a similar study was performed in CIN.…”
Section: Mirnas As Novel Biomarkers For Akimentioning
confidence: 99%
“…Risk of bias is mainly derived from the index test. The conduct or interpretation of the index test introduced high risk in 6 records [ 7 , 8 , 17 , 19 , 23 , 28 ] and unclear risk in 13 articles [ 6 , 14 – 16 , 18 , 20 , 21 , 25 27 , 29 31 ].…”
Section: Resultsmentioning
confidence: 99%